1975
DOI: 10.1042/cs0490613
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Uric Acid Concentration Related to the Urinary Excretion of Aldosterone and of Electrolytes in Normal Subjects

Abstract: 1. The relations between the concentration of plasma uric acid and urinary excretion of aldosterone, sodium and potassium, were studied in ten healthy males on a diet containing 160 mmol of sodium and 90 mmol of potassium per day. 2. Plasma uric acid correlated positively with aldosterone excretion and this correlation was statistically independent of sodium and potassium excretion. 3. Plasma uric acid correlated positively with potassium excretion and negatively with the urinary sodium/potassium ratio. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…5 There was a trend for the plasma uric acid to correlate positively with potassium excretion and negatively with Na/K ratio in urine after diuretic administration, but this reached significance only when the mean plasma uric acid from the two study periods was correlated with the furosemide diuretic response (Tables 11 and Ill), thereby confirming a previous observation. 3 Similar relationships between plasma uric acid and urinary electrolyte excretion have been noted in normal subjects without any stress 14 and after administration of aldosterone antagonists. 15 Although plasma uric acid concentration and electrolyte excretion appear to relate under several different circumstances and partially explain intersubject variation in diuretic response, the relationships observed in this study were too weak for them to be of practical value.…”
Section: Discussionmentioning
confidence: 53%
“…5 There was a trend for the plasma uric acid to correlate positively with potassium excretion and negatively with Na/K ratio in urine after diuretic administration, but this reached significance only when the mean plasma uric acid from the two study periods was correlated with the furosemide diuretic response (Tables 11 and Ill), thereby confirming a previous observation. 3 Similar relationships between plasma uric acid and urinary electrolyte excretion have been noted in normal subjects without any stress 14 and after administration of aldosterone antagonists. 15 Although plasma uric acid concentration and electrolyte excretion appear to relate under several different circumstances and partially explain intersubject variation in diuretic response, the relationships observed in this study were too weak for them to be of practical value.…”
Section: Discussionmentioning
confidence: 53%
“…Studies in humans have also found an association of plasma renin activity (PRA) and serum uric acid in patients with essential hypertension125 and PRA is higher in hyperuricaemic compared with normouricaemic children 126. Plasma uric acid level has also been reported to correlate positively with aldosterone excretion to the urine in healthy men 127. In a renal biopsy study, a correlation of uric acid with the percentage of renin positive juxtaglomerular cells was also found 128.…”
Section: Introductionmentioning
confidence: 94%
“…In acute situations plasma albumin concentration and plasma uric acid (Steele, 1969) show changes in a similar direction with changes in extracellular volume. It has been suggested that the usual plasma uric acid concentration in healthy subjects may be determined to some extent by the customary dietary intake of sodium, the latter influencing extracellular fluid volume (Ramsay et al, 1975). If the usual plasma albumin is similarly influenced, then the correlation observed could be explained on this basis.…”
Section: In Vivo Ultrafiltrationmentioning
confidence: 99%